RICHARD HOOKER'S VIA MEDIA DOCTRINE OF SCRIPTURE AND TRADITION - Gibbs, Lee W. (2002)
In two earlier articles published in Harvard Theological Review,“Richard Hooker's Via Media Doctrine of Justification,” HTR 74 (1981) 211–20, and “Richard Hooker's Via Media Doctrine of Repentance,” HTR 84 (1991) 59–74. I argued the thesis that the thought of Richard Hooker (1544–1600) represents a distinctive via media way of doing theology that immeasurably influenced what would later become known as “Anglicanism.” This thesis has recently been vigorously challenged by a certain group of scholars who constitute what may now well be regarded as a “new school” of Hooker interpretation.The leader of this new school is W. J. Torrance Kirby, whose revisionist interpretation is clearly set forth in Richard Hooker's Doctrine of the Royal Supremacy (Leiden and New York: Brill, 1990) 33–37, 126–27; “Richard Hooker as an Apologist of the Magisterial Reformation in England,” in Richard Hooker and the Construction of Christian Community (ed. Arthur Stephen McGrade; Tempe, Ariz.: Medieval & Renaissance Texts & Studies, 1997) 220–23; and “Richard Hooker's Theory of Natural Law in the Context of Reformation Theology,” Sixteenth Century Journal 30 (1999) 681–703. See also Nigel Atkinson, Richard Hooker and the Authority of Scripture, Tradition and Reason: Reformed Theologian of the Church of England (Carlisle, Cumbria: Paternoster, 1997); and “Hooker's Theological Method and Modern Anglicanism,” Churchman 114 (2000) 40–70. These scholars argue that the via media understanding of Hooker's thought, along with his anachronistic association with what only much later became known as “Anglicanism,” were largely creations of “Catholicizing” leaders of the nineteenth-century High Church Oxford Movement—including Hooker's editor, John Keble, and most notably John Henry Newman in his pre-conversion Anglo-Catholic guise. These scholars then set forth their counterthesis that Hooker is to all intents and purposes a faithful English exponent of all the basic “orthodox” doctrines of the Magisterial Reformers, namely, Luther and especially Calvin.